EPIZOIC FAUNA ON THE FLATHEAD LOCUST LOBSTER, THENUS ORIENTALIS (LUND) - Lazarus, R J; Reddy, P Sita Rami; Thangavelu, R (Indian Journal of Fisheries, 2011)
The incidence of sessile barnacles (Balanus amphitrite communis) and pedunculate cirripeds Octolasmis warwickii and O. tridens) on the carapace and of O. cor var. A, O. co/- var. B and O. cor var. C in the branchial chamber of Thenus orientalis are reported